Come sing, Jimmy Jo - Paterson, Katherine (New York : Dutton, 1985)
When his family becomes a successful country music group and makes him a featured singer, eleven-year-old James has to deal with big changes in all aspects of his life, even his name.
"Lodestar books.".
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
4.9
4.9
Keywords: Country music -- Fiction; Family life -- Fiction; Musicians -- Fiction; Country music -- Fiction; Family life -- Fiction; Musicians -- Fiction